Active and intelligent packaging in meat industry. (March 2017) - Fang, Zhongxiang; Zhao, Yanyun; Warner, Robyn D.; Johnson, Stuart K.
Abstract: Background: Microbial contamination and lipid and protein oxidation are major concerns for meat and meat products in terms of food safety and quality deterioration. The meat quality and safety properties are highly dependent on packaging materials and technologies. Scope and approach: To achieve longer shelf life, active packaging and intelligent packaging have been developed to change the conditions of the package, impart information, monitor the product supply chain, and provide anti-counterfeit functionality. This will effectively enhance food safety and quality and consequently increase the product value, convenience, and consumer satisfactions. This review analyzes the recent developments in active and intelligent packaging in the meat industry, in both research and commercial domains. The global patents and future research trends are also discussed. Key findings and conclusions: Active and intelligent packaging offer great opportunities for enhancing meat safety, quality, and convenience, and consequently decrease the number of retailer and consumer complaints. Some important factors such as legislation concerns (e.g. migration of active substances from packaging materials, labelling), economics and consumers' preferences should be considered to successfully implement antimicrobial and intelligent packaging solutions in the meat industry. Highlights: Meat quality and safety are highly dependent on packaging technology. Active packaging positively changes the internal conditions of packaging. Intelligent packaging monitors product conditions and information exchange. Active and intelligent packagings enhance meat quality and safety.